Between Blindness and Touching. Jacques Derrida and Jean-Luc Nancy on the Self-Portrait - Meer, Julia (Labyrinth: An International Journal for Philosophy, Value Theory and Sociocultural Hermeneutics, 2021)
The paper analyzes Jacques Derrida’s and Jean-Luc Nancy’s concept of the self-portrait. It is argued that Nancy builds on Derrida’s approach but introduces two decisive modifications. Firstly, he develops the emergence of the painter on the canvas as constitution of the self – an aspect Derrida does not consider. Secondly, Nancy understands portraying – and thus images – on the basis of touching. In contrast, Derrida conceives portraying as coming from the invisible and two forms of blindness. In doing so, he remains ex negativo in a tradition which links images to vision, whereas Nancy tries to overcome it. Nancy’s alterations not only lead to a modified theory of the self-portrait but also refine Derrida’s influential concept of différance by highlighting its corporeal and ontological dimension.